Cutaneous Tuberculosis: Clinicopathologic Arrays and Diagnostic Challenges. (9th July 2018) - Khadka, Priyatam; Koirala, Soniya; Thapaliya, Januka
Abstract : The clinicopathological manifestations of cutaneous tuberculosis are diverse. The precise diagnosis is often overlooked, due to clinical presentations as those of cutaneous diseases with different etiology and the relative paucity of the pathogens in the lesions. Meanwhile, almost all of the diagnostic methods confer lower sensitivity and specificities which augments further diagnostic challenges. This article revises the current scenario of the disease's physiopathology and underscores clinicopathological challenges, due to multifaceted presentations of cutaneous tuberculosis, in the diagnosis.